2016
DOI: 10.2166/wpt.2016.040
|View full text |Cite
|
Sign up to set email alerts
|

Performance and operating experiences of the first Scandinavian full-scale Discfilter installation for tertiary phosphorus polishing with preceding coagulation and flocculation

Abstract: Microscreening (using Discfilters) is a widely used technology for suspended solids removal in tertiary effluent streams of wastewater treatment plants. Several pilot studies have shown the feasibility of using coagulation and flocculation in combination with microscreens for advanced phosphorus removal, but the number of full-scale references is still limited. In summer 2014, the first Scandinavian full-scale Discfilter installation with 2-stage chemical pre-treatment (coagulation and flocculation) was starte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…50 to 70% of TSS (mg/L) remaining after PST can be removed if the MS mesh size is selected between 15 and 4 µm. In contrast, studies conducted by Remy et al, Köngsepp et al, and Vaananen et al [41][42][43] mainly observed the removal of solids from raw wastewater using drum or disc filters, with mesh sizes predominantly ranging from 100 to 400 µm but with the help of chemicals such as ferric chloride and aluminum chloride or sulfate. However, the idea of coupling a PST with an MS in order to extract a higher amount of POC (mg/L) out of municipal WWTPs without any chemical addition is being introduced for the first time in this study.…”
Section: Solids Distribution In the Effluent Of Pstmentioning
confidence: 96%
“…50 to 70% of TSS (mg/L) remaining after PST can be removed if the MS mesh size is selected between 15 and 4 µm. In contrast, studies conducted by Remy et al, Köngsepp et al, and Vaananen et al [41][42][43] mainly observed the removal of solids from raw wastewater using drum or disc filters, with mesh sizes predominantly ranging from 100 to 400 µm but with the help of chemicals such as ferric chloride and aluminum chloride or sulfate. However, the idea of coupling a PST with an MS in order to extract a higher amount of POC (mg/L) out of municipal WWTPs without any chemical addition is being introduced for the first time in this study.…”
Section: Solids Distribution In the Effluent Of Pstmentioning
confidence: 96%
“…Among the biofilm separation methods, microscreens maximize the process compactness (Ødegaard et al 2010). Although the TSS separation by microscreens with woven media has been studied for a decade (Persson et al 2006;Mattsson et al 2009;Rossi et al 2013), chemical pre-treatment is a more recent development (Kängsepp et al 2016;Väänänen et al 2016;Langer et al 2017). Coagulation and flocculation before disc filters allow TSS and phosphorus removal above 90%, while keeping a high filtration flux and having limited footprint requirements.…”
Section: Introductionmentioning
confidence: 99%